2020
DOI: 10.3389/fimmu.2020.01455
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 4 (TLR4)/Opioid Receptor Pathway Crosstalk and Impact on Opioid Analgesia, Immune Function, and Gastrointestinal Motility

Abstract: Toll-like receptor 4 (TLR4) recognizes exogenous pathogen-associated molecular patterns (PAMPs) and endogenous danger-associated molecular patterns (DAMPs) and initiates the innate immune response. Opioid receptors (μ, δ, and κ) activate inhibitory G-proteins and relieve pain. This review summarizes the following types of TLR4/opioid receptor pathway crosstalk: (a) Opioid receptor agonists non-stereoselectively activate the TLR4 signaling pathway in the central nervous system (CNS), in the absence of lipopolys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
102
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(107 citation statements)
references
References 124 publications
(236 reference statements)
3
102
0
2
Order By: Relevance
“…Potential interactions can occur between TLR4 and opioid receptors (μ, δ and κ). These interactions are involved in immune function, opioid analgesia, and intestinal motility ( 25 ). The TLR4 signaling pathway was directly activated by opioid receptor agonists in the CNS in the absence of LPS, indicating interactions within the cell membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential interactions can occur between TLR4 and opioid receptors (μ, δ and κ). These interactions are involved in immune function, opioid analgesia, and intestinal motility ( 25 ). The TLR4 signaling pathway was directly activated by opioid receptor agonists in the CNS in the absence of LPS, indicating interactions within the cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms may include inhibiting inflammation and oxidative stress ( 24 ). Moreover, TLR4 and opioid receptor interactions occur in the central nervous system (CNS), and effects on peripheral immune cells have also been demonstrated ( 25 ). However, whether butorphanol can regulate macrophage polarization in sepsis-induced ALI is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…µ opioid receptor activation attenuates the increase in in ammatory cytokines. δ opioid receptor (DOR) activation inhibits the production of NO and increases superoxide dismutase (SOD) and GSH-Px activity (Zhang, Yang et al 2020). Different internal and external reasons effects on qeering antioxidant enzyme in opioid consumptions such as dose, duration of treatment, drug interaction and de ciency of drug biotransformation in different disease (Hsiao, Chang et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…µ opioid receptor activation attenuates the increase in in ammatory cytokines. δ opioid receptor (DOR) activation inhibits the production of NO and increases superoxide dismutase (SOD) and GSH-Px activity (Zhang, Yang et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…151,189,190 In addition, brain organoid studies have revealed imbalanced excitatory/inhibitory neurotransmission, 72,73,88,93 which could further elucidate how chronic opioid exposure increases glutamatergic signaling. 153,154 Furthermore, HDPs shared commonly upregulated genes with those who have PTSD, AD, PD, and HD, including those related Lin et al, 109 Pavoni et al, 110 Gonzalez et al, 111 Meyer et al, 112 Arber et al, 113 Ghatak et al, 114 Perez et al, 115 Yan et al, 116 Yoon et al, 137 Zhang et al, 138 Zhou et al, 139 Janssens et al, 140 Nowakowski et al, 141 Allodynia, hyperalgesia, NF-κB activation 180,[183][184][185][186][187] to oxidative phosphorylation and metabolic pathways (ATP5D, ATP5H, HSD17B10/NDUFB11, NDUFA8, NDUFB7). 151 Opioid exposure additionally caused dysregulated programmed cell death, synapse organization, cell morphogenesis, brain volume, and neuron differentiation, 152,169,191 similar to several of the above brain organoid studies.…”
Section: Neurodegenerative Disordersmentioning
confidence: 99%